IMPLIKASI PENGUNGKAPAN BEBAN CORPORATE SOCIAL RESPONSIBILITY PADA KINERJA PASAR PERUSAHAAN YANG TERDAFTAR DI BEI - Wini, Ni Wayan Septia; Wirakusuma, Made Gede; Sari, Maria M. Ratna (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.08.TAHUN 2017DO - 10.24843/EEB.2017.v06.i08.p06, 2017)
The purpose of this study was to obtain empirical evidence of the influence of CSR disclosure of expenses on the market performance of companies listed on the BEI and examine the differences in market performance of financial and non-financial companies that revealed the expenses of CSR in BEI. The population in this study are the financial and non financial companies listed on the Stock Exchange in 2011-2015. The sampling method that used is purposive sampling method. The samples consisted of 11 financial companies and 18 non-financial companies. Analysis technique used is simple linear regression test and independent sample t-Test. The test results show there is a significant negative influence between the disclosure of CSR expenses with market performance of the companies listed on the BEI. Also found that there are differences in the performance of financial markets and non-financial companies that disclose their CSR expense.
Keywords: The Disclosure of CSR Expenses, Market Performance, Financial Companies, Non-Financial Companies.